A Lexical Semantic Study of Chinese Opposites - Ding, Jing (Frontiers in Chinese Linguistics,, 2018)
This book studies Chinese opposites. It uses a large corpus (GigaWord) to trace the behavior of opposite pairings' co-occurrence, focusing on the following questions: In what types of constructions, from window-size restricted and bi-syllabic to quad-syllabic, will the opposite pairings appear together? And, on a larger scale, i.e. in constrained-free contexts, in which syntactic frames will the opposite pairings appear together? The data suggests aspects that have been ignored by previous theoretical studies, such as the ordering rules in co-occurrent pairings, the differences between the three main sub-types of opposites (that is, antonym, complementary, converse) in discourse function distributions. The author also considers the features of this Chinese study and compares it to similar studies of English and Japanese. In all, it offers a practical view of how opposites are used in a certain language as a response to the puzzles lingering in theoretical fields. This study appeals to linguists, computational linguists and language-lovers. With numerous tables, illustrations and examples, it is easy to read but also encourages readers to link their personal instincts with the results from a large corpus to experience the beauty of language as a shared human resource. .